Pharmacokinetics of Cannabidiol, Cannabidiolic Acid, Δ9-Tetrahydrocannabinol, Tetrahydrocannabinolic Acid and Related Metabolites in Canine Serum After Dosing With Three Oral Forms of Hemp Extract - Wakshlag, Joseph J.; Schwark, Wayne S.; Deabold, Kelly A.; Talsma, Bryce N.; Cital, Stephen; Lyubimov, Alex; Iqbal, Asif; Zakharov, Alexander (Frontiers in Veterinary Science, 2020)
Hemp extract use is increasing in veterinary medicine with little examination of serum cannabinoids. Many products contain small amounts of 9-tetrahydrocannabinol (THC), and precursor carboxylic acid forms of CBD and THC known as cannabidiolic acid (CBDA) and tetrahydrocannabinolic acid (THCA). Examination of the pharmacokinetics of CBD, CBDA, THC and THCA on three oral forms of hemp extract that contained near equal amounts of CBD and CBDA, and THC and THCA in dogs was performed. In addition, we assess the metabolized psychoactive component of THC, 11-hydroxy-9-tetrahydrocannabinol (11OH-THC) and CBD metabolites 7-hydroxycannabidiol (7OH-CBD) and 7-nor-7 carboxycannabidiol (7COOH-CBD) to better understand the pharmacokinetic differences between three formulations regarding THC and CBD, and their metabolism. Six purpose bred female beagles were utilized for study purposes, each having an initial 7-point, 24 hour pharmacokinetic study performed using a dose of 2 mg/kg body weight of CBD/CBDA (~1 mg/kg CBD and ~1 mg/kg CBDA), dogs were then dosed every 12 hours for 2 weeks and had further serum analyses at week 1 and 2, 6 hours after the morning dose to assess serum cannabinoids. Serum was analyzed for each cannabinoid or cannabinoid metabolite using liquid chromatography and tandem mass spectroscopy (LC-MS/MS). Regardless of the oil form, or chew provided, the 24-hour pharmacokinetics for CBD, CBDA, and THCA were similar, with only oil B generating enough data within the lower limit of quantitation to assess pharmacokinetics of THC. CBDA and THCA concentrations were two to three-fold higher than CBD and THC concentrations, respectively. The one- and two-week steady state concentrations were not significantly different between the two oils or the soft chew forms. CBDA concentrations were statistically higher with oil B than the other forms, showing superior absorption/retention of CBDA. Furthermore, oil A showed less THCA retention than either the soft chew or oil B at weeks 1 and 2. 11OH-THC was below the quantitation limit of the assay for nearly all samples. Overall, these findings suggest CBDA and THCA are absorbed or eliminated differently than CBD or THC respectively, and that a partial lecithin base provides superior absorption and/or retention of CBDA and THCA.